1991
DOI: 10.1017/s0950268800067571
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ceftriaxone on faecal flora: analysis by micromorphometry

Abstract: SUMMARYIn order to elucidate the effect of ceftriaxone therapy on the morphology of gut microflora, 11 human volunteers were treated with ceftriaxone, 1 g daily, given intramuscularly in one dose. Treatment continued for 5 days. Faecal microflora was analysed by digital image processing before, during and after the treatment period.We derived simple numerical parameters which describe the morphologic composition of the flora. They were significantly influenced by the antibiotic, and returned to their baseline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…The first application of image analysed microscopy to the intestinal microflora focused on morphometry, and in particular the determining the effects of antibiotics on the gut microbial ecology (21)(22)(23). To achieve this, a video camera was mounted on the microscope and connected to an image capture board (a "frame-grabber") in a personal computer.…”
Section: Morphometrymentioning
confidence: 99%
See 1 more Smart Citation
“…The first application of image analysed microscopy to the intestinal microflora focused on morphometry, and in particular the determining the effects of antibiotics on the gut microbial ecology (21)(22)(23). To achieve this, a video camera was mounted on the microscope and connected to an image capture board (a "frame-grabber") in a personal computer.…”
Section: Morphometrymentioning
confidence: 99%
“…It allows measurement of many flora parameters without the need for culturing. Several applications have been developed in Groningen, initially just to perform automated counting and morphometric analysis (21)(22)(23), later adding fluorometric analysis as well, including immunofluorescence measurements (2,3,(12)(13)(14)(15) and more recently fluorescence in situ hybridization (FISH) (4). In this paper we will review the progress made in the microbiological image processing programme in Groningen.…”
Section: Introductionmentioning
confidence: 99%
“…This new method called digital image processing (DIP), developed and described by Meijer and colleagues [1][2][3] and Wilkinson and colleagues [4], enables detection and quantitative as well as qualitative analysis of bacterial objects in faeces, based on their morphological appearances. Analysis is determined by the distribution of bacterial species present in faeces at the highest concentration only; these are obligate anaerobic bacteria which normally reach concentrations of 1O°-10"1 micro-organisms per gram faeces [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…stool specimens of mice contain large numbers of fusiform shaped bacteria whereas small rod shaped and coccoid bacteria are predominant in human faeces. Differences have also been described between rodent animal species [7,8] as well as between human individuals [3,9,10]. In humans, van der Merwe and colleagues [11] showed that genetically identical individuals (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…With this approach significant changes in the fraction, with more than 107 bacteria/g, can be measured. Meijer's method is for example very useful for accurate monitoring of the intestinal (faecal) microflora during antibiotic treatment [13]. However, for the detection of small but essential changes in the composition of the faecal flora, such as may be caused by dietary changes, the sensitivity of morphological analysis of faecal flora needs to be increased.…”
Section: Introductionmentioning
confidence: 99%